Phase Pattern Calibration for Interferometric Applications in Spaceborne SAR Systems - Markus Bachmann; Marco Schwerdt; Gabriel Castellanos Alfonzo; Dirk Schrank (International Journal of Antennas and Propagation)
SAR is a widely used technique to acquire images for geoscience and earth observation applications. Active phased array antennas are commonly used in spaceborne SAR systems. For certain modes and applications, it is necessary to know the phase behavior of these phased array antennas. For applications utilizing the different polarization channels for interferometry, the phase difference between the polarizations needs to be calibrated very accurately as it is the main evaluation parameter. Also for single-pass interferometric missions, the difference between the two antennas in terms of phase gradients is of major importance. This paper demonstrates for the first time the usage of phase patterns in an operational interferometric SAR mission. It describes why these phase patterns are required and how they are used to fulfill the different goals of the missions. Then, the mathematical model to derive the phase of the antenna patterns is shown. Finally, the paper explains how the antenna patterns are calibrated in order to minimize their residual errors and describes in detail the measurements performed for this calibration and verification.